The Effect of Perceived Organizational Support on Employee Engagement and Turnover Intention: The Mediating Role of Organizational Commitment - Clarisa Nindya Franselina; Ignatius Soni Kurniawan; Mohammad Ahyar Syafwan Lysander (Jurnal Komunikasi dan Bisnis, 2025)
Previous studies have reported inconsistent findings regarding the role of organizational commitment in explaining the relationship between perceived organizational support, employee engagement, and turnover intention, particularly in public service organizations. This study examines the influence of perceived organizational support on employee engagement and turnover intention at the Yogyakarta Central Post Office, while testing organizational commitment as a mediating variable. A quantitative survey was conducted with 50 respondents, and the data were analyzed using Partial Least Squares (PLS). The results show that perceived organizational support has a significant positive effect on employee engagement and organizational commitment, and a significant negative effect on turnover intention. However, the bootstrapping results for the indirect paths indicate that organizational commitment does not significantly mediate the relationship between perceived organizational support and either employee engagement or turnover intention, so the mediation hypothesis is not supported. These findings indicate that perceived organizational support plays a direct role in enhancing employee engagement and reducing turnover intention, while suggesting that other factors such as job satisfaction, intrinsic motivation, and leadership style may also influence employees’ decisions to remain with or leave the organization.